Apples and chalk dust / Juan Primitivo Pulido Petrola. - Petrola, Juan Primitivo Pulido (Pangasinan : [s.n.], 2017)
"Apples and Chalk Dust: The Ideal versus Reality of Mentoring Mentors" was piloted in the Archdiocese of Lingayen - Dagupan Catholic Schools to determine the lived experiences of ALDCS teachers with the ideal against their personal experiences about being mentored by their Learning Area Coordinators. The study is qualitative in nature and used descriptive phenomenology as its research design. The informants were chosen through purposive sampling.
Bibliography: pages 98-103.
CHED-La Union
Keywords: Teaching -- Aids and devices